Public-private co-operation for gas provision in poor neighbourhoods of Buenos Aires: Impact on housing improvements and health - Cynthia Goytia; Ricardo Pasquini; Pablo Sanguinetti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study examines the programme Redes Solidarias, a public-private initiative that connected to natural pipelined gas 4,000 households in the Great Buenos Aires Area during 2005. The main features of the institutional framework are described and the main results of an impact estimation analysis are reported. The mechanism of selection of neighbourhoods for the connection represents a 'natural experiment', which allows the estimation of the causal effects of the programme on several indicators, including housing improvements, health and happiness related variables. We perform this analysis using data from two surveys we collected on the neighbourhoods in 2006 and 2007. The programme was found to generate improvements on dwelling walls, and the installation of hot water in the bathroom. A significant reduction of cases of flu, fever and other respiratory diseases is also found. Finally, the programme is found to improve the satisfaction reported by people with respect to their dwellings.
Keywords: H43; I31; I38; O22; 330; infrastructure provision; gas; impact evaluation